First Report of Barley Stripe Mosaic Virus Infecting Barley (Hordem Vulgare L.) In Al-Jabal Al-Akhdar- Libya - Soad Omar,; Zainap Easa,; Asma Abed-Alsaed, (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. The study aimed to assess the presence of barley stripe virus isolated from the willow field in Al-Jabal Al-Akhdar for the first time in Libya. Methods. The barley stripe mosaic virus (BSMV) field tested and the virus was transferred by mechanical transfer technique. The virus was identified using cytological assays and the polymerase chain reaction (PCR). Results. A survey was conducted to detect infection with Barley mosaic virus (BSMV) in a field in Al-Safsaf, Al-Jabal Al-Akhdar, during the months of February and March of 2022. Symptoms associated with the virus were identified, as well as infection was confirmed using the polymerase chain reaction (PCR) technique. Tests showed the presence of the BSMV virus in the field where the Barley crop was surveyed. The virus was transmitted mechanically to the host, Hordeum vulgare vr. ACSAD1877, where the virus was multiplied. The characteristics of the BSMV isolate were studied, and thin sections of Barley leaves infected with the BSMV isolate were examined. Some changes were evident. The cellular activity associated with the infection, including the change in the shape of the chloroplasts and the appearance of cytoplasmic internal particles in which the virus particles are concentrated, while the nucleus was not affected by the infection or showed particles of the virus. BSMV isolate with a genetic content of RNA divided into parts with molecular weights of 3 and 2.5 kb for each of the alpha and beta genome parts. The alpha and beta genome parts were amplified separately using the polymerase chain reaction (PCR) technique, using specialized primers for each part of the parts. The genome and when ten different cutting enzymes were added to the alpha and beta parts of the genome, the different patterns of the cutting became clear, which reflect the difference in the nucleotide sequences involved in building the different parts, and this confirms that the parts are not similar and confirms that the virus has many genetic components. Conclusion. Our findings suggest the importance of identifying viruses that infect grassy crops of important economic importance in Libya, including barley and wheat, because these viruses are pathogenic pests that cause heavy losses to these crops.